Utility of serum concentration of protein S100 at admission to the medical intensive care unit in prediction of permanent neurological injury - Knapik, Piotr; Knapik, Małgorzata; Partyka, Robert; Broll, Iwona; Cieśla, Daniel; Wawrzyńczyk, Maciej; Kokocińska, Danuta; Jałowiecki, Przemysław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Admission to the intensive care unit (ICU) may be preceded by dramatic events leading to permanent neurological injury. Plasma S100 protein levels are proved to be clinically useful in predicting neurological outcome following cardiac arrest. It is unclear, however, whether this may be extrapolated to a broader population of ICU patients. Aim : To assess the utility of plasma S100 protein in predicting death, permanent neurological damage, or unfavourable outcome at admission to the intensive care unit. Material and methods: The concentration of plasma S100 protein was established in 102 patients on admission to the ICU, regardless of their neurological status and the reason for admission. The majority of patients were admitted with various cardiac diseases, excluding trauma patients. The patients were classified into three groups with the following binary outcomes: permanent neurological deficit or restoration of consciousness; unfavourable outcome (death or survival with permanent neurological deficit) or favourable outcome; and death or survival. Results: Plasma S100 protein levels at admission facilitated the identification of patients who later developed a permanent neurological deficit or regained consciousness (p < 0.0001). All patients with plasma S100 protein over 0.532 µg/l at ICU admission either developed a permanent neurological deficit or had an unfavourable outcome (death or survival with permanent neurological deficit). However, sensitivity for this cut-off value was only 48% and 40%, respectively. Conclusions: Plasma S100 protein levels over 0.532 µg/l are specific but not sensitive for both permanent neurological deficit and unfavourable outcome when assessed in a heterogeneous population at admission to the ICU.